The experience of Malaysian occupational therapists in conducting home assessments and home visits with older clients - Romli, Muhammad Hibatullah; Mackenzie, Lynette; Tan, Maw Pin; Lovarini, Meryl; Clemson, Lindy (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2017)
Introduction: Home visits are complex processes for clients and occupational therapists. Despite the benefits of home visits, the numbers of home visits being conducted are decreasing in international settings due to service constraints or client reluctance. Published international studies may not be applicable to Malaysia due to cultural and geo-demographic differences relating to the home context. This study aimed to explore the experience of occupational therapists in Malaysia in conducting home visits. Materials and Methods: A focus group discussion was conducted with seven occupational therapists in one teaching hospital in Kuala Lumpur. The group session was audio-recorded, transcribed, summarised and analysed using thematic analysis. Results: Themes developed were: i) client factors inhibiting effective service provision, ii) uninformed policies and guidelines, and iii) professional identity and growth. Conclusions: Our study has revealed major challenges for Malaysian occupational therapists with regards to conducting home visits. Future studies should now evaluate factors underlying reluctance to participate in home visits and effective strategies to overcome these difficulties.